2015
DOI: 10.1007/s12328-015-0570-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil may induce prolonged severe anemia during pegylated-interferon/ribavirin/simeprevir therapy in liver transplant recipients

Abstract: Aim: Pegylated-interferon/ribavirin/simeprevir (PEG-IFN/RBV/SMV) combination therapy is widely used for hepatitis C virus (HCV) treatment after liver transplantation (LT). Here, we observed two cases of extended severe anemia during PEG-IFN/RBV/SMV therapy for HCV serological type 1 re-infected after LT. Immunosuppressants consisted of tacrolimus and mycophenolate mofetil (MMF). Case 1 was a 65-year-old-woman treated with PEG-IFN/RBV/SMV therapy and 500 mg MMF/day 9 months after LT. Her serum hemoglobin (Hb) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In Case 2, because the hemoglobin level was already low, the dosage of rEPO was increased from 100 μg to 150 μg during ribavirin therapy, and although the patient developed mild anemia, a blood transfusion was not required. As several previous reports have suggested that the interaction between MMF and ribavirin could induce anemia, the progression of anemia seen in Case 2 might have reflected this interaction.…”
Section: Discussionmentioning
confidence: 63%
“…In Case 2, because the hemoglobin level was already low, the dosage of rEPO was increased from 100 μg to 150 μg during ribavirin therapy, and although the patient developed mild anemia, a blood transfusion was not required. As several previous reports have suggested that the interaction between MMF and ribavirin could induce anemia, the progression of anemia seen in Case 2 might have reflected this interaction.…”
Section: Discussionmentioning
confidence: 63%
“…Diarrhea is a common adverse event after the administration of cyclosporine and tacrolimus [ 27 ]. Anemia is a known adverse event associated with tacrolimus and mycophenolate mofetil [ 28 , 29 ]. Previous studies have reported severe cold agglutinin hemolytic anemia and severe persistent anemia with immunosuppressant administration, requiring the need for careful monitoring of treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical significant drug-drug interactions with DAA have not been reported for mycophenolate mofetil. However, persistent anemia with need of blood cell transfusions was reported due to combined treatment with mycophenolate mofetil and peg-IFN/RBV/SMV[94]. …”
Section: Drug-drug Interaction Between Daa’s and Immunosuppressionmentioning
confidence: 99%